The insecurity. Modifications in the ethical structure - Barraza Barraza, Laurencia; Barraza Soto, Isidro (Avances en Supervisión Educativa, 2018)
This research article provides some findings about the perception of elementary school children from third to sixth grade in Durango City, Mexico, in relation to public insecurity, mainly in relation to violence. It is a qualitative work; the case study method was used; the questionnaire as an instrument was used for this research and the interview as a research technique. The subjects were two elementary school children of 9 and 12 years old respectively. Among the findings, this research shows that there is an association between security and lockup; the school is perceived as a safe place, empathy seems diminished, the idea of community is dispelled and geographical ethic evidence was found.